The Role of the Family in Facing the Impact of Advances in Information Technology on the Lives of Children and Adolescents (Review of Islamic Psychology) - Dwi Estiningsih (Al Misykat : Journal of Islamic Psychology, 2023)
Change is a natural thing in life, as well as changes in technology always occur along with the development of science. Technological changes have affected many aspects of life, including family life. The family as the most basic social organization inevitably has to adapt to all changes. Currently, the development of information technology has reached various areas of life and has become a primary need for every family. However, the parties most vulnerable to receiving negative impacts are children and adolescents. The family plays a central role in overseeing the development of children amidst the pace of technological change. This paper will review the impact of technological advances on family life, especially for the growth and development of children and adolescents in a review of Islamic Psychology. The role of the family in replacing the fulfillment of needs which is the motive for children and adolescents to use the internet is also discussed using the Uses Gratification theory. This U G theory identifies five groups of basic needs in media, namely cognitive needs (obtaining information, knowledge, and understanding), affective needs (emotions, pleasure/satisfaction, and feelings), personal integrative needs (credibility, stability, and status), the need for social integration (interacting with friends, family, etc.), and the need for tension relief (escape and diversion).